Pohon Bidara (Ziziphus mauritiana Lamk) dalam Tafsir AlQur’an serta Analisis Manfaatnya sebagai Obat Anti-Kanker Alami - Majid, Alima Fadhila (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2023)
The use of bidara has developed from time to time. As technology develops, the use of bidara can be found in the world of medical treatment. This is what interests the writer to find out about the use of bidara as a natural anti-cancer drug and the interpretation of bidara trees reviewed in the Qur'an, sura Saba' verse 16. In this study, the author used a qualitative approach with the Library Research technique. The method used is descriptive-analysis. The primary source in this study is the book of Tafsir Ibn Katsîr and the secondary sources are magazines or articles, journals and scientific works related to research. The results of this study are the use of active compounds contained in bidara leaves, namely alkaloids, sapori, tani, and steroids. According to Jannah's research results (2018), sea bidara leaf extract has the potential to inhibit the growth of breast cancer cells (1470) in vitro with values of ethanol extract, chloroform fraction, and n-hexane fraction of 5814, Mn, and 384 respectively. The katsir regarding the bidara in surah Saba': 16 states that the bidara (As-Sidr) in the sentence Min sidrin qalīl (a few bidara trees) in this context Ibn katṡīr interprets the pronunciation of As-Sidr as a substitute for good trees because of the disbelief of the Saba people '